Comparing the Effectiveness of the Ability to Enjoy Educational Package with the PERMA Well-Being Educational Package and the Time Perspective Educational Package on the Academic Burnout of Adolescents - Marashi, Saedeh; Bahramipour Isfahani, Mansoureh; Golparvar, Mohsen (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The aim of the present study was to compare the effectiveness of the ability to enjoy educational package with the PERMA well-being educational package and the time perspective educational package on the academic burnout of adolescents. Methods and Materials: The current research was a semi-experimental type of pre-test-post-test and follow-up with a control group. The statistical population consisted of all high school students who had veteran parents in the academic year of 2021-2022 in Isfahan City. For this aim, 72 students were selected by purposeful sampling and randomly assigned to three experimental groups (18 people) and a control group (18 people). Individuals of the experimental groups participated in parallel and simultaneous training sessions on the ability to enjoy, PERMA well-being and time perspective; But for the control group, there was no intervention. The measuring tool included the academic burnout questionnaire of Berso et al. (1997). This is measuring three areas of academic fatigue, academic apathy and academic ineffectiveness. For data analysis, the statistical method of repeated measurements analysis of variance, along with Bonferroni’s post-hoc test, was employed using SPSS-24 software. Findings: The results showed that all three training packages were effective on pessimism, training on the ability to enjoy and PERMA on emotional exhaustion in students with veteran parents (p<0.05), but these three training packages were not effective on academic burnout of these students (p<0.05). The findings of this research emphasize the importance of paying attention to the academic vitality of children of veterans and have important practical implications for educational interventions useful for them. Conclusion: According to the results of the present research, it is possible to suggest the use of these two educational packages to managers, teachers and counselors to reduce the academic burnout of adolescents.